2012
DOI: 10.1080/14786419.2011.564584
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and antimicrobial activity of volatile constituents fromQuercus leucotrichophora(Fagaceae) bark

Abstract: The chemical composition of the volatile extract (yield ≈ 0.13%, v/w) from the bark of Quercus leucotrichophora (Fagaceae) was analysed for the first time by GC-MS. Twenty-three constituents, amounting to 93.0% of the total detected contents of the volatile extract, were identified. The volatile extract contained approximately 86.36% monoterpenoids, 6.53% sesquiterpenoids and 0.11% aliphatic aldehydes. 1,8-Cineol (40.359%) followed by γ-terpinene (16.369%) were the major monoterpene constituents of the volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Previously, the antimicrobial profile of the volatile extract of QLB was recorded against three microbial cultures, namely; Streptococcus pyogenes, Streptococcus aureus, and Escherichia coli. The volatile extract of QLB exhibited a potential antimicrobial activity against Streptococcus pyogenes, compared to Streptococcus aureus, and Escherichia coli [14]. The antibacterial activity of the fatty acid methyl ester (FAME) extract of QL fruits was recorded against four bacterial stains namely; Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli from a range of 7.8 to 15.9 mm [15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, the antimicrobial profile of the volatile extract of QLB was recorded against three microbial cultures, namely; Streptococcus pyogenes, Streptococcus aureus, and Escherichia coli. The volatile extract of QLB exhibited a potential antimicrobial activity against Streptococcus pyogenes, compared to Streptococcus aureus, and Escherichia coli [14]. The antibacterial activity of the fatty acid methyl ester (FAME) extract of QL fruits was recorded against four bacterial stains namely; Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli from a range of 7.8 to 15.9 mm [15].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, active compounds like, quercetin and kaempferol were isolated from the ethanolic stem bark extract of QL, whereas the antimicrobial activity of the extract showed highest activity against E. coli followed by S. aureus, P. auroginosa and B. subtilis, respectively [13]. Further, the presence of twenty-three phytoconstituents (major phytocomponent: monoterpenoids) in the volatile extract of bark of QL were analyzed by GC-MS analysis [14]. The fruit extract of QL revealed the presence of higher amount of saturated fatty acid compared to unsaturated fatty acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the exact mechanisms of herbal medicines in traditional medication are still not well-understood but it is reported that the herbal constituents could act as nutraceuticals, immunomodulators, boost body oxidant status or provide antioxidant compounds, prevent attachment of microbes as well as halt the proliferation or multiplication of microorganisms and some might act as microcidals. 17 So far, various medicinal plants have been studied for their antibacterial activities such as Butea monosperma, Actinidia macrosperma, 18 Quercus leucotrichophora, 19 Medicago sativa, 20 Citrullus colocynthis, 21 Dorema ammoniacum, 22 Eupatorium glandulosum, 23 Tetracarpidium conophorum, 24 Ficus capensis, 25 Terminalia chebula, 26 Verbascum sinuatum, 27 Gymnema sylvestre, 28 Curcuma zedoaria, 29 Berberis heterophylla, 30 Mimosa pudica 31 and Nelumbo nucifera. 32 Phytotherapy of different diseases using natural medicinal herbs has no well-reported toxicity in comparison with chemotherapy by synthetic drugs.…”
Section: Phytotherapeutic Modalitiesmentioning
confidence: 99%
“…There have been many topics of bark utilization research. However, bark research can be divided into two main objectives: utilization of their main components (cellulose, lignin, and hemicellulose) (Fengel and Wegener 1989;Usta 1993;Balaban and Ucar 2001;Odabaş-Serin and Gümüşkaya 2006;Safdari et al 2011;Miranda et al 2012;Akgül et al 2013;Serin and Güleç 2014;Durmaz et al 2016;Gönültaş and Uçar 2017), and their secondary metabolite qualities (Sjödin et al 1996;Kuliev et al 1997;Vrkočová et al 2000;Diouf et al 2009;Yesil-Celiktas et al 2009;Duda-Chodak et al 2011;Lee et al 2011;Maimoona et al 2011;Sati et al 2012;Legault et al 2013;Bouras et al 2015;Devappa et al 2015;Hofmann et al 2015;Özgenç et al 2016;Özgenç et al 2017;Dróżdż and Pyrzynska 2018).…”
Section: Introductionmentioning
confidence: 99%